Penguatan Peran Kader Posyandu Dalam Penanganan Kasus Stunting Melalui Edukasi dan Pelatihan PMT Berbasis Sinbiotik - Komalasari, Husnita; Yunita, Lina; Adinda Putri, Destiana; Komalasari, Zulkarnaen; Darasinta Arlina, Gehtin (Lembaga Dongan Dosen, 2025)
Malnutrition is a category of disease that includes malnutrition, obesity or excess body weight and micronutrient deficiencies. Indonesia, especially Sintung village has a high percentage of malnutrition sufferers, especially malnutrition or stunting. In order to reduce the number of stunting sufferers and support the government's program, namely zero stunting, to realize an “Indonesia Emas 2045”, Community Service (PKM) activities are needed which aim to increase the role of posyandu cadres in dealing with stunting in Sintung village. The steps taken include conducting outreach and training regarding the knowledge of posyandu cadres and mothers of toddlers regarding stunting, probiotics and prebiotics as well as making synbiotic-based PMT, namely cookies and yoghurt, using lecture, discussion and work practice methods. To measure the success of the activity, pre and post-test questionnaires were filled out. The results showed that there was an increase in participants' knowledge regarding stunting, probiotics and prebiotics as well as how to make synbiotic-based PMT in the form of yoghurt and cookies according to the material presented by the resource person.